Students' Mathematical Investigation: A Review Based on Disposition and Self-Esteem - Usi Salsiah; Elsa Komala; Rani Sugiarni (Universitas Suryakancana, 2025)
Students' mathematical investigation ability is not only influenced by cognitive knowledge, but also by affective factors such as mathematical disposition and self-esteem. This study aims to analyze the effect of mathematical disposition on students' mathematical investigation ability, analyze the effect of self-esteem on students' mathematical investigation ability, and analyze the effect of mathematical disposition and self-esteem on students' mathematical investigation ability. This study uses a quantitative approach. The population of the study was 49 students of class XI of a private high school in Cianjur Regency in the 2024/2025 academic year. The sample in this study was class XI-1 selected by purposive sampling. The research instruments were mathematical disposition and self-esteem questionnaires, as well as students' mathematical investigation ability tests on circle material. In addition, interviews were conducted with several students to strengthen the results of the mathematical investigation test. The data analysis techniques used included simple linear regression tests and multiple linear regression tests, by first ensuring that the classical assumptions were met. The results of the study showed that there was a significant influence between mathematical disposition and mathematical investigation ability of 40.2%. Meanwhile, self-esteem did not have a significant effect on mathematical investigation ability, with a contribution of 18.7%. Simultaneously, mathematical disposition and self-esteem had a significant effect on students' mathematical investigation ability, with a contribution of 31.6%. This finding emphasizes the importance of strengthening mathematical disposition in learning to improve students' mathematical investigation ability